History of subjectivity in dispositif: changing arrangements of Vietnamese teachers' meeting through lesson study for learning community. Issue 1 (2nd January 2022) - Tsukui, Atsushi; Saito, Eisuke
ABSTRACT: This study examined research–practice partnerships (RPP) as a place where teachers (re)shape their discourses in a distinctive working arrangement through our case in Vietnam. In particular, it explored the concept of subjectivity in dispositifs, focusing on a heterogeneous ensemble of discursive and nondiscursive arrangements of collective activities formulating its members' patterns of thought, practice, and identity. We present the historical roots of dispositif in Vietnamese schools and locate a new one in our RPP. There are two categories of dispositif in organizations from the Vietnamese public sector: assembly and gathering. We added a model of Lesson Study for Learning Community (LSLC) as a dispositif from Japan. The assembly is an authorized place for the members to convey information in a hierarchical order, while the gathering represents occasions for discussing issues in an egalitarian manner. The arrangements of discursive and socio-material conditions of the LSLC allowed the teachers to engage in equal and free discussions relying on their own emotions. Our case suggests that exploring dispositif of schools could improve the design of teacher professional learning through RPP.